The role of stress hormones in dental management behavior problems - Dušková, M; Vašáková, J; Dušková, J; Kaiferová, J; Broukal, Z; Stárka, L (Physiological research, 2017)
Dental management behavior problems are thought to be both multifactorial and multidimensional, consisting of physiological, behavioral and cognitive components. The stress response to pain or even the anticipation of distress initiates activation of the hypothalamic-pituitary-adrenal axis and causes an increase of cortisol and catecholamines. The literature on the role of hormones in dental management behavior problems comprises about one hundred papers, which have mainly been focused on this activation of the HPA axis in various situations in dental care. They have generally used salivary cortisol as a marker of the activity of the HPA axis, sometimes combined with salivary alpha amylase. Here we summarize the literature data on the role of stress hormones in dental management behavior problems.
Keywords: Hydrocortisone; Hypothalamo-Hypophyseal System; management bolesti; bolest; lidé; Humans; Pain; Stress, Psychological; strach; systém hypotalamus-hypofýza; zubní lékařství; Fear; Saliva; systém hypofýza - nadledviny; psychický stres; sliny; Dentistry; hydrokortison; Pain Management; Pituitary-Adrenal System